Changes in female football players` in-season training load, intensity and physical performance: training progression matters more than accumulated load - Savolainen, E. H. J.; Ihalainen, J. K.; Vänttinen, T.; Walker, S. (Frontiers in Sports and Active Living, 2024)
Introduction: This observational study investigated: (1) potential changes in female football players` in-season training load, intensity and physical performance, and (2) if in-season accumulated training load, intensity, or their progression are associated to changes in physical performance.